Electroanatomic mapping system guided his bundle pacemaker implantation: experience of the his bundle registry graz. (19th May 2022) - Rohrer, U; Prenner, G; Sereinigg, M; Manninger, M; Geczy, T; Bisping, E; Eberl, A; Lercher, P; Zirlik, A; Scherr, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with bradyarrhythmia in need for ventricular pacing may suffer from pacing-induced heart failure due to unphysiological right ventricular pacing. His bundle pacing (HBP) allows to overcome this common issue with a more physiologic approach but real-life procedural data using this technology is scarce. Methods: We report a single centre experience of the first 44 consecutive patients being implanted with a His-bundle-based pacemaker 09/2020-11/2021 per 3D-mapping guided implantation due to different types of bradyarrhythmia, or for cardiac resynchronisation therapy in heart failure combined with a left-ventricular lead (HOT-CRT) ± a right ventricular defibrillator lead. The positioning of the His-bundle-lead was done by identifying the His-bundle-location with a 3D electroanatomic mapping system via an introducing sheath that is provided with electrodes at its tip. Results: Mean age was 70 [16;86] years, 12/44 (27%) patients were female, mean baseline LVEF was 44±18%. Baseline ECG was captured: QRS width was 123±33ms, with typical LBBB in 14/44 (32%), typical RBBB in 4/44 (9%), alternating BBB in one patient (2%) and either no BBB or ventricular escape rhythm in 25/44 (57%). Indications for implantation were AV-block grade II-III in 19/44 (43%), primary prophylactic ICD indication in HFrEF in 13/44 (30%), atrial fibrillation with bradycardic conduction in 7/44 patients (16%), sick-sinus-syndrome in 4/44 (9%) and secondary prophylactic ICD indication in one patient (2%). In 41/44 (93%) a primary device was implanted, in 3/44 (7%) a pre-existent device was upgraded with a HB lead. Therefore, 14 dual-chamber-pacemaker, 5 single-chamber-pacemaker, 8 single-chamber CRT-P, 11 dual-chamber CRT-P, 4 single-chamber CRT-D, 2 dual-chamber CRT-D were implanted. In 50 patients HBP was attempted, while in 6/50 (12%) patients outside of this analysis the attempt was not successful, these patients were consecutively implanted with a non-HBP-device and therefor excluded from the further analysis. In the 44 patients included in this analysis with primary successful HBP, 4/44 (9%) his-bundle-leads dislocated within the first 48 hours, leading to a secondary success rate of 91%. There were two post-procedural pneumothorax that needed drainage, no major procedure-related complications occurred. Median skin-to skin procedure time was 109±50 minutes. The paced QRS width at the post-implantation follow up was 115±32ms with a change in QRS width of -10ms (+72;-92ms). When excluding the secondary lead dislocations and including only the successful HB paced QRS complexes, the paced QRS width was 105±30ms and the change in QRS width was -12±42ms. The mean his-bundle threshold was 1, 2±1V over 0, 5ms (0, 5;1, 5ms). The proportion of ventricular pacing was 69±38%. Conclusion: Electroanatomic-guided His bundle pacing is feasible, with high implantation success rate and electric impact, both regarding QRS width and pacing threshold.